2014
DOI: 10.1371/journal.pone.0088289
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Dysfunction Improved in Heroin-Dependent Men after Methadone Maintenance Treatment in Tianjin, China

Abstract: ObjectiveTo investigate whether methadone maintenance treatment (MMT) is correlated with sexual dysfunction in heroin-dependent men and to determine the prevalence and risk factors of sexual dysfunction among men on MMT.MethodsThe study included a retrospective survey and a cross-sectional survey which contained interviews of 293 men who are currently engaged in MMT. The results of the two surveys were compared. For a subset of 43 participants, radioimmunoassay was additionally conducted using retrospective an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 27 publications
2
19
2
Order By: Relevance
“…On one side, the rate of heroin-dependent patients suffering from hypo-sexuality and erectile dysfunction was reported to have significantly increased after methadone maintenance treatment with respect to the prevalence measured before opioid substitution therapy [12,13] . On the other hand, in a more recent study, Zhang et al [14] found a decrease in the severity of sexual dysfunction in association with methadone maintenance initiation. Moreover, in this study, methadone dose and duration of methadone treatment were not found to be associated with sexual dysfunction, casting doubts upon a direct negative effect of the opioid agonist medications on the sexual function.…”
Section: Introductionmentioning
confidence: 88%
“…On one side, the rate of heroin-dependent patients suffering from hypo-sexuality and erectile dysfunction was reported to have significantly increased after methadone maintenance treatment with respect to the prevalence measured before opioid substitution therapy [12,13] . On the other hand, in a more recent study, Zhang et al [14] found a decrease in the severity of sexual dysfunction in association with methadone maintenance initiation. Moreover, in this study, methadone dose and duration of methadone treatment were not found to be associated with sexual dysfunction, casting doubts upon a direct negative effect of the opioid agonist medications on the sexual function.…”
Section: Introductionmentioning
confidence: 88%
“…Although a correlation between opioids and sexual dysfunction has been established, no study has yet found any dose-response relationship between testosterone level and opioid consumption (Gerra et al, 2015;Gulliford, 1998;Zhang et al, 2014). The link between buprenorphine -a partial-opioid agonist -and testosterone levels, has not been clearly established, as many results are contradictory (Bliesener et al, 2005;Gulliford, 1998;Hallinan et al, 2009).…”
Section: 0discussionmentioning
confidence: 99%
“…More recent studies have also shown the lower impact of methadone on sexual dysfunction than heroin. In men, sexual dysfunction can even be reduced after methadone treatment initiation (Babakhanian et al, 2012;Zhang et al, 2014), with the exception of premature ejaculation (Chekuri et al, 2012). To date, only four studies on sexual dysfunction have focused on buprenorphine -perhaps because buprenorphine is available in fewer countries than methadone -and only one of these included women.…”
Section: 0introductionmentioning
confidence: 99%
“…According, literature reported that opioid patients could experience orgasm dysfunction, a lack of intercourse satisfaction, less sexual desire and a diminished satisfaction after the initiation of methadone treatment [43,44].…”
Section: Due To the Positive Correlation Found Between Every Health Dmentioning
confidence: 99%